2007
DOI: 10.1021/om700264w
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Oxidation of Monoterpenes:  Novel Aerobic Pd(II)/Cu(II)-Catalyzed Oxidation of Linalool under Chloride-Free Nonacidic Conditions

Abstract: Linalool, a monoterpenic allylic alcohol, has been efficiently and selectively oxidized by dioxygen in methanol and ethanol solutions using a chloride-free Pd(OAc)2/Cu(OAc)2 catalytic system under nonacidic conditions. Corresponding allylic ether arising from the exclusive oxidation of a trisubstituted internal double bond has been characterized as a major product in each alcohol. In methanol, this product, 7-methoxyhotrienol, was obtained in virtually quantitative yield. It is remarkable that a monosubstitute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…In addition, we found that the electron effect of enones' substituents had a profound impact on the yields of the reaction. For the same indole, enones with electron-donating substituents would give higher yields than those with electron-withdrawing substituents (entries [8][9][10][11], and the trend also applied to indoles. Interestingly, the enones with ortho-substituents afforded higher yields than those with para-substituents (entries 10 and 11).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, we found that the electron effect of enones' substituents had a profound impact on the yields of the reaction. For the same indole, enones with electron-donating substituents would give higher yields than those with electron-withdrawing substituents (entries [8][9][10][11], and the trend also applied to indoles. Interestingly, the enones with ortho-substituents afforded higher yields than those with para-substituents (entries 10 and 11).…”
Section: Resultsmentioning
confidence: 95%
“…The bifunctional, bimetallic catalysts have been applied to various organic transformations in recent decades, [1 -3] such as cyanation, [4] Friedel-Crafts acylation, [5] Friedel-Crafts alkylation, [6 -8] oxidation, [9] hydroformylation, [10] allylic etherification, [11] nitro-Mannich reaction [12] and other rections. [13 -15] Heterobimetallic catalysts offer superior results in terms of efficiency and selectivity relative to the individual ones.…”
Section: Introductionmentioning
confidence: 99%
“…After carrying out the reaction and cooling to room temperature, the excess of oxygen was slowly vented from the autoclave. The products were isolated by a column chromatography (silica gel 60) using mixtures of hexane and CH 2 Cl 2 as eluents and identified by 1 H, and 13 C NMR and/or GC-MS.…”
Section: Typical Proceduresmentioning
confidence: 99%
“…The oxidation of natural olefins by dioxygen in systems type Wacker (PdCl 2 /CuCl 2 ) is limited because the CuCl 2 reoxidant acting as a Lewis acid, promote undesirable carbon skeletal rearrangements of those substrates, which are accompanied by nucleophilic addition of chloride ions and or protic solvents [23]. The selectivity reported for the oxidation product in those reactions does not exceed 25% [24].…”
Section: General Aspectsmentioning
confidence: 99%